2000
DOI: 10.1074/jbc.275.15.11412
|View full text |Cite
|
Sign up to set email alerts
|

A Cartilage Oligomeric Matrix Protein Mutation Associated with Pseudoachondroplasia Changes the Structural and Functional Properties of the Type 3 Domain

Abstract: Cartilage oligomeric matrix protein (COMP) is a member of the thrombospondin family of extracellular matrix glycoproteins. All members of the family contain a highly conserved region of thrombospondin type 3 sequence repeats that bind calcium. A mutation in COMP previously identified in a patient with pseudoachondroplasia resulted in abnormal sequestration of COMP in distinctive rER vesicles. The mutation, Asp-446 3 Asn, is located in the type 3 repeats of the molecule. This region was expressed in a mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 42 publications
7
54
0
Order By: Relevance
“…The structure of TSP2 is also Ca 2ϩ -sensitive based on its susceptibility to trypsin proteolysis (19). Sedimentation velocity experiments of TSP1 (13) and recombinant Ca 2ϩ -binding repeats of TSP5/COMP (20) revealed an increase in the sedimentation coefficient upon the addition of Ca 2ϩ , which is consistent with a change in structure upon Ca 2ϩ binding. Adhesion of cells to TSP1 (21,22) and TSP2 (19) is Ca 2ϩ -dependent, as is TSP1 inhibition of cathepsin G (23) and neutrophil elastase (24).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…The structure of TSP2 is also Ca 2ϩ -sensitive based on its susceptibility to trypsin proteolysis (19). Sedimentation velocity experiments of TSP1 (13) and recombinant Ca 2ϩ -binding repeats of TSP5/COMP (20) revealed an increase in the sedimentation coefficient upon the addition of Ca 2ϩ , which is consistent with a change in structure upon Ca 2ϩ binding. Adhesion of cells to TSP1 (21,22) and TSP2 (19) is Ca 2ϩ -dependent, as is TSP1 inhibition of cathepsin G (23) and neutrophil elastase (24).…”
supporting
confidence: 49%
“…1); ESI, electrospray ionization; G2, recombinant C-terminal globule of TSP2 (residues 947-1172); LC, liquid chromatography; MALDI-TOF, matrix-assisted laser desorption/ionization time of flight; MS, mass spectrometry; tCaG2, recombinant C-terminal portion of hTSP2 from within the Ca 2ϩ -binding repeats to the end of TSP2 (residues 718 -1172, Fig. 1 (18,20,29).…”
mentioning
confidence: 99%
“…Equilibrium dialysis of E3Ca indicated that 23-25 Ca 2ϩ ions bind to the Ca 2ϩ -binding repeats. This is higher than what has been observed for TSP-1, TSP-5, and TSP-5 constructs (13)(14)(15)(16)21) but is in agreement with the values predicted by the crystal structure (9) and what has been determined for TSP-2 constructs by atomic absorption spectroscopy (22). Trp-698, which is quenched upon the addition of Ca 2ϩ , is at position 7 of a putative motif (Fig.…”
Section: The Tr1 Constructs Contain An Intact Tb 3ϩ -Binding Site-mentioning
confidence: 43%
“…Evidence for such intracellular protein complexes also comes from cartilage biopsies of individuals with chondrodysplasia caused by mutations in COMP (Maddox et al, 2000;Merritt et al, 2007). In these individuals and in cell culture models expressing selected mutant variants, the retention of misfolded COMP leads to coretention of other ECM components, including collagens (types II, IX and XI) (Hecht et al, 2005;Maddox et al, 1997;Vranka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%